Strategic Partnerships and Supply Chain Responsiveness: Implications for Operational Performance in Indonesia’s Petrochemical Sector - Holis, Nurul; Santosa, Wahyuningsih; Dewayana, Triwulandari Satitidjati (Universitas KH. Abdul Chalim Mojokerto, 2026)
This research investigates the influence of strategic supplier partnerships and customer relationships on supply chain responsiveness and their subsequent impact on operational performance within Indonesia’s petrochemical and plastic sectors. A quantitative approach using structural equation modeling was applied to data collected from 170 supply chain professionals. The results indicate that both strategic supplier partnerships and customer relationships significantly improve supply chain responsiveness, which positively drives operational performance. However, demand uncertainty weakens these relationships, reducing the effectiveness of collaborative practices under volatile market conditions. The findings extend the literature by demonstrating how demand uncertainty shapes the effectiveness of relational strategies in volatile emerging markets. The unique contribution of this study lies in empirically validating a moderated mediation model that integrates relational, capability based, and environmental perspectives, offering practical insights for enhancing supply chain resilience.